THE CORRELATION BETWEEN LISTENING STRATEGIES AND LISTENING ACHIEVEMENT OF SEVENTH GRADERS AT SMP TRI DHARMA PALEMBANG - Niken Rizky Anwari; Nike Angraini (Didascein : Journal of English Education, 2022)
The purpose of this research was to find out (1) whether there was any significant correlation between listening strategies and listening achievement; (2) the most effective strategies being used by the students. The writers applied quantitative research method as design method. The results of the Pearson’s Product Moment correlation test showed that the obtained correlation coefficient data r-obtained (0.403) was higher than r- table (0.329). The level of probability (p) (sig.2-tailed) was 0.013. It means that p (0.013) was lower than 0.05, there was a medium correlation between the students’ listening strategies and listening achievement. It can be interpreted that the seventh-grade students realize that their listening strategies was very important and influential in the listening process. The researchers concluded that the use of strategy in listening was important, because the students can perform their listening activity better and well-structured if they applied strategy in their listening process. The strategy that commonly used by the students was metacognitive strategy. Those strategies are effective in helping students in their listening process. This study succeeded in investigating the correlation between listening strategies and listening comprehension and it impacts toward the seventh-grade students of SMP Tri Dharma Palembang in the academic year 2021/2022.